2014
DOI: 10.1002/jts.21974
|View full text |Cite
|
Sign up to set email alerts
|

Acquired Equivalence in U.S. Veterans With Symptoms of Posttraumatic Stress: Reexperiencing Symptoms Are Associated With Greater Generalization

Abstract: The severity and number of reexperiencing symptoms (e.g. flashbacks) show considerable variability across individuals with post-traumatic stress disorder. One interpretation of reexperiencing symptoms invokes generalization: specifically, the traumatic memory may be stored in such a way that neutral stimuli that only vaguely resemble some feature of the traumatic event are sufficient to trigger the memory. If this is the case, then individuals with higher levels of reexperiencing symptoms might show greater ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 7 publications
2
18
0
Order By: Relevance
“…Consistent with these observations, we have found that genetically enhancing integration of adult-born DGCs is sufficient to enhance Consistent with these ideas, a recent study found a positive correlation between re-experiencing the traumatic event and the degree of fear overgeneralization in individuals with PTSD (Kostek et al, 2014).…”
Section: Adult Hippocampal Neurogenesis and Maintenance Of Memory Presupporting
confidence: 88%
“…Consistent with these observations, we have found that genetically enhancing integration of adult-born DGCs is sufficient to enhance Consistent with these ideas, a recent study found a positive correlation between re-experiencing the traumatic event and the degree of fear overgeneralization in individuals with PTSD (Kostek et al, 2014).…”
Section: Adult Hippocampal Neurogenesis and Maintenance Of Memory Presupporting
confidence: 88%
“…Increased generalization has now been observed in three different studies of PTSD: in the first study, participants recruited from the same Veteran population as the current study were assessed on an acquired equivalence task (Kostek et al, 2014), and in the second, trauma-exposed individuals from a very different population (individuals with clinically-diagnosed PTSD and a single exposure to trauma) were assessed on a contextual processing task (Levy-Gigi et al, 2015). The current study assessed a different type of generalization: the ability to transfer learning when relevant stimulus features remain stable and irrelevant stimulus features are altered.…”
Section: Discussionmentioning
confidence: 85%
“…Participants were 60 Veterans from VA New Jersey Health Care System in East Orange, NJ (11.2% female, mean age 54.0 years, SD 10.3, mean education 14.4 years, SD 2.6) and from the same population used in our prior acquired equivalence study (Kostek et al, 2014). Thirty-eight Veterans (63.3%) self-identified as African-American, 18 (30.0%) as Caucasian, and the remaining 4 (6.7%) as Other or Mixed-race; 7 (13.7%) self-identified ethnicity as Hispanic.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations